Rivalitas Suami Istri Dalam Kontestasi Pemilihan Kepala Desa - Achmad Nashrudin P; Enjum Jumhana (Res Justitia : Jurnal Ilmu Hukum, 2022)
The election of the Village Head (Pilkades) is a democratic phenomenon that has been a tradition since colonial times (Muis, 2006). As a phenomenon, the journey has been long enough until the reign of Joko Widodo period 2. The practice of democracy, requiring deliberation for consensus, based on the belief in family and gotong royong aimed at welfare that contains religious elements, based on truth, love and noble ethics and upholding the principles of democracy is equality, freedom, and pluralism. This paper aims to look at the background of the contestation of husband and wife in pilkades, its influence on the quality of democracy and the quality of political participation of rural communities. Using qualitative methods through phenomenological approaches and descriptive analysis, the results of the analysis, obtained the results of the analysis, that the opportunity to serve more than 2 times as Village Head in accordance with Law No. 6 of 2014 on Villages and the prohibition of single candidates, as well as the will to rule more than 2 times became the main reason husband and wife conducted a "fake" rivalry. Rivalries that ostensibly promote equality, equality and gender bias, undermine and degrade the value of democracy itself